Philosophie asiatique/Asian philosophy
VIII, 411 p.
Keywords: The present publication is a continuation of two earlier series of chronicles, Philosophy in the Mid-Century (Firenze 1958/59) and Contemporary Philosophy (Firenze 1968), edited by Raymond Klibansky. As with the earlier series the present surveys purport to give a survey of significant trends in contemporary philosophical discussion. The need for such surveys has, I believe, increased rather than decreased over the last years. The philosophical scene appears, for various reasons, rather more complex than ever before. The continuing process of specialization in most branches, the emergence of new schools of thought, particularly in philosophical logic in the philosophy of language, and in social and political philosophy, the increasing attention being paid to the history of philosophy in discussions of contem porary problems as well as the increasing interest in cross-cultural philosophical discussion, are the most important contributory factors. Surveys of the present kind are a valuable source of knowledge about this complexity and may as such be of assistance in renewing the understanding of one's own philosophical problems. The surveys, it is to be hoped, may help to strengthen the Socratic element of modern philosophy, the world wide dialogue or Kommunikationsgemeinschaft. So far, six volumes have been prepared for the new series. The present surveys in Asian Philosophy (Vol. 7) follow the surveys in the Philosophy of Language and Philosophical Logic (Vol. I), Philosophy of Science (Vol. 2), Philosophy of Action (Vol. 3), Philosophy of Mind (Vol. 4), African Philosophy (Vol. 5), and Medieval Philosophy Part 1-2 (Vol. 6).